Assess of residual mechanical resistance of reinforced concrete beams after fire - Pereira, Renato Guilherme; Pires, Tiago Ancelmo Carvalho; Duarte, Dayse; Rego Silva, José Jeferson (Revista ALCONPAT, 2018)
This paper presents an experimental program to determine the residual strength of simple supported reinforced concrete beams subject to bending after fire. Also presented is a three-dimensional, nonlinear finite element model capable of predicting the thermal and mechanical (residual) behavior of this type of structural element. The beams presented up to 120 min. of fire exposure, a good performance after fire, not having a significant reduction in their residual resistance, and the numerical model was accurate in the prediction of the temperatures and the residual burst load when compared to the experimental results.